Analysis of Students' Mental Workload with NASA-TLX in Project-Based Learning Implementation - Luthfi Firdaus; Yuningsih Yuningsih; I Wayan Ardi Sumarta (Program Pascasarjana STIE Amkop Makassar, 2025)
This study maps students' mental workload during Project-Based Learning (PjBL) on a Human Resource Information Systems (HRIS) project by focusing on NASA-TLX measurements. The issue raised is the imbalance between project challenges and students' cognitive capacity during the troubleshooting and system integration phases. The study aims to describe the level of mental workload in aggregate and per dimension, while linking it to instructional design decisions. The method used is a descriptive quantitative survey of 21 students, with the unweighted NASA-TLX procedure (paired comparisons and a rating of 0–100 per dimension). The results show that the global mental workload is in the medium–high category. The Mental Demand, Temporal Demand, and Effort dimensions are most prominent; Frustration increases in the critical phase; Performance tends to be medium; while Physical Demand is the lowest. The internal reliability of the instrument is very high (α ≈ 0.951). These findings emphasize the need for redistribution of workload across milestones, reduction of extrinsic workload through technical scaffolding (decision-tree, template, checklist), and fast-feedback as strategies to reduce Frustration without reducing cognitive challenges. This study positions NASA-TLX not just as a diagnostic tool, but as a design compass to keep PjBL challenging, measurable, and humane.